The Influence of Problem Base Learning Model on Improving Psychomotor Abilities of Automotive Engineering - Ilham Yuliady; Zulfadli Fadli; Rahmadani; Yogi Dian Alfana; Erik Fernandes (Jurnal Vokasi Mekanika (VoMek), 2026)
Automotive education as a field of vocational education emphasizes the development of psychomotor skills through authentic and industry oriented practical learning. However, practical instruction in automotive workshops is often dominated by conventional teacher centered approaches, resulting in limited student engagement and suboptimal skill development. This study aims to analyze the effect of the Problem Based Learning (PBL) model on improving the psychomotor skills of automotive engineering students in practical learning. A quasi experimental method with a pretest–posttest control group design was employed. The research sample consisted of two classes of automotive engineering students from the 2025 cohort, selected using purposive sampling as the experimental and control groups. Psychomotor skill data were collected using a performance-based assessment instrument covering work procedure accuracy, tool operation skills, occupational safety, and the quality of practical outcomes. Data analysis was conducted using descriptive statistics and an independent t-test with a significance level of a = 0.05. The results indicate that students who participated in Problem Based Learning achieved higher average psychomotor skill scores than those who received conventional instruction. Hypothesis testing confirmed a statistically significant difference between the two groups (t_calculated > t_table). These findings demonstrate that Problem-Based Learning is effective in enhancing students’ psychomotor skills through contextual problem-solving activities, active learning engagement, and meaningful hands-on practice. This study provides empirical evidence supporting the implementation of problem-based instructional models in automotive vocational education and offers practical implications for improving the quality of practice-based learning aligned with industry competency demands.